2011
DOI: 10.4218/etrij.11.0110.0106
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Fault Injection Using Simulator Modification Technique

Abstract: In the current very deep submicron technology era, fault tolerant mechanisms perform an essential function to cope with the effects of soft errors. To evaluate the effectiveness of the fault tolerant mechanism, reliability engineers use simulated fault injections using either saboteur modules or mutants in the simulation model. However, the two methods suffer from both inefficiency in the simulation mechanism and difficulties with the experimental setups. To overcome these inefficiencies, we propose the Verilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…VITAL defines two levels of support. VITAL level 0 requires the definition of a level 0 attribute (line 21 of Listing 1), using ports of type std ulogic and std logic vector with no underscores in the port names (lines [18][19], and special naming convention for timing generics (lines 8-11, with ports names prefixed as tpid -interconnect path delay that represents the delay between components-and tpd -propagation delay that represents the pin-to-pin delay within a component). Compliance with VITAL level 0 provides SDF back annotation and negative timing constraints.…”
Section: The Vital Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…VITAL defines two levels of support. VITAL level 0 requires the definition of a level 0 attribute (line 21 of Listing 1), using ports of type std ulogic and std logic vector with no underscores in the port names (lines [18][19], and special naming convention for timing generics (lines 8-11, with ports names prefixed as tpid -interconnect path delay that represents the delay between components-and tpd -propagation delay that represents the pin-to-pin delay within a component). Compliance with VITAL level 0 provides SDF back annotation and negative timing constraints.…”
Section: The Vital Standardmentioning
confidence: 99%
“…Alternative SBFI approaches proposed the development of non-standard simulators to speed-up the simulation of faults, like the one targeting IcarusVerilog models [19] or those using GPGPUs [15]. However, these approaches are not generic and cannot be applied to off-the-shelf EDA tools.…”
Section: Introductionmentioning
confidence: 99%
“…The second group investigated tool acceleration to reduce the simulation time, wherein the tool identifies and removes unnecessary or redundant operations of the SFI , . One such approach is to use an efficient SFI management strategy, which uses a CF mechanism.…”
Section: Overview Of the Acceleration Of The Fault Injection Techniquesmentioning
confidence: 99%
“…From our experience with SFI, when we performed fault‐injection campaigns with a large number of faults and various injection locations, times, and complex co‐simulation targets, we found that some parts of the SFI process were redundant , . If we can remove the redundant process in the SFI campaign, we may be able to accelerate the test time of the SFI.…”
Section: Introductionmentioning
confidence: 99%
“…Three basic categories of fault injection include hardware implemented fault injection, software implemented fault injection and simulated fault injection. Advantages of simulated fault injection include cost reduction in the design process due to early diagnosis, avoidance of redesign in case of error and thus short time-to-market [13], [14]. Very high speed integrated circuits Hardware Description Language [VHDL] based fault injection receives wide spread recognition due to its flexibility combined with a high degree of controllability and observability on all the components of the simulated model [12].…”
Section: Introductionmentioning
confidence: 99%